Management of Airway Obstruction due to Diffuse Idiopathic Skeletal Hyperostosis in the Cervical Spine: A Case Report and Literature Review - Yoshimatsu, Yuki; Tobino, Kazunori; Maeda, Ken; Kubota, Kensuke; Haruta, Yohei; Adachi, Hiroshi; Abe, Toshiyuki; Masunaga, Tomoka; Sueyasu, Takuto; Osaki, Toshihiro (Internal Medicine, 2019)
Diffuse idiopathic skeletal hyperostosis (DISH) is a relatively common progressive noninflammatory entheses disease. Patients are often asymptomatic or are undiagnosed due to minor chronic symptoms. We herein report a rare case in which the primary symptom was sudden-onset upper airway obstruction due to exuberant osteophytosis in the cervical spine. Treatment was successful with careful airway management and surgical osteophyectomy. Most DISH cases in the literature with airway obstruction have been managed with tracheotomy. However, the safety and necessity of this approach remain questionable. We herein discuss the possibility of conservative management as a choice of airway control. Airway obstruction due to DISH may be underrecognized. This highlights the importance of including DISH in the differential diagnosis of airway obstruction. In addition, a detailed evaluation and personalized care for each individual case is essential.